Evaluasi Usability Pada Website PT. Bali Art Furniture Menggunakan Metode Webuse - Laksmi, Ida Ayu Nyoman; Erawan, Marchia Easti Putri; Dharmawan, Made Gede Wawan; Gunawan, I Made Agus Oka; Indrawan, Gede (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2024)
PT Bali Art Furniture is a company that sells furniture and home decoration with an international market. The company has two websites, Bali Art Furniture and Bali Home Decoration, which have been operating since 2021 but have never been evaluated. This evaluation aims to improve user convenience based on four criteria: Content, Organization and Readability, Navigation and Links, User Interface Design, and Performance and Effectiveness. Based on the evaluation results using the Webuse method with the Content, Organization and Readability criteria, Bali Art Furniture scored 0.866, while Bali Home Decoration scored 0.868. On Navigation and Links, Bali Art Furniture scored 0.892 and Bali Home Decoration 0.895. On User Interface Design, Bali Art Furniture 0.886, and Bali Home Decoration 0.885. For Performance and Effectiveness, Bali Art Furniture 0.853 and Bali Home Decoration 0.857. In addition, this evaluation provides recommendations in the form of real data for improving the two websites according to the criteria evaluated.Keywords: Evaluation; Usability; Website; Webuse; FurnitureÂ AbstrakPT. Bali Art Furniture merupakan perusahaan yang menjualan mebel dan dekorasi rumah dengan pasar internasional. Perusahaan memiliki dua website, Bali Art Furniture dan Bali Home Decoration, yang telah beroperasi sejak 2021 namun belum pernah dievaluasi. Evaluasi ini bertujuan untuk meningkatkan kenyamanan pengguna yang dilakukan berdasarkan empat kriteria: Content, Organization and Readability, Navigation and Links, User Interface Design, serta Performance and Effectiveness. Berdasarkan hasil evaluasi menggunakan metode Webuse dengan kriteria Content, Organization and Readability, Bali Art Furniture mendapat skor 0,866, sedangkan Bali Home Decoration 0,868. Pada Navigation and Links, Bali Art Furniture 0,892 dan Bali Home Decoration 0,895. Di User Interface Design, Bali Art Furniture 0,886, dan Bali Home Decoration 0,885. Untuk Performance and Effectiveness, Bali Art Furniture 0,853 dan Bali Home Decoration 0,857. Selain itu evaluasi ini memberikan rekomendasi berupa data real perbaikan kedua website tersebut sesuai dengan kriteria yang dievaluasi.Â